Social Interaction and Stock‐Market Participation - Hong, Harrison; Kubik, Jeffrey D.; Stein, Jeremy C. (Journal of Finance, 2004)
ABSTRACT We propose that stock‐market participation is influenced by social interaction. In our model, any given “social” investor finds the market more attractive when more of his peers participate. We test this theory using data from the Health and Retirement Study, and find that social households—those who interact with their neighbors, or attend church—are substantially more likely to invest in the market than non‐social households, controlling for wealth, race, education, and risk tolerance. Moreover, consistent with a peer‐effects story, the impact of sociability is stronger in states where stock‐market participation rates are higher.